2015
DOI: 10.1155/2015/280167
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a CUPRAC-Based HPLC Postcolumn Assay and Its Applications forGinkgo bilobaL. Extracts

Abstract: The aim of the present work was to improve and validate the HPLC-CUPRAC postcolumn method for the evaluation of active antioxidant markers from the acetonic extracts of Ginkgo biloba leaves. Improvement of the HPLC online assay was performed by evaluating the suitable loop temperature, the reaction loop length, and the impact of flow rate. Separation of the analytes was performed by the HPLC method on an ACE C18 analytical column using a gradient elution program. The separated antioxidant markers in the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Rimkiene et al. (2015) identified quercetin as the antioxidants expressed as TEAC values from Ginkgo biloba extract. Copper was reduced primarily by quercetin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rimkiene et al. (2015) identified quercetin as the antioxidants expressed as TEAC values from Ginkgo biloba extract. Copper was reduced primarily by quercetin.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant mechanism works using the mechanism that involves the reduction of Cu 2+ to Cu 1+ (Latos-Brozio et al, 2021). Rimkiene et al (2015) identified quercetin as the antioxidants expressed as TEAC values from Ginkgo biloba extract. Copper was reduced primarily by quercetin.…”
Section: Tpc and Antioxidant Activitymentioning
confidence: 99%
“…The raw material was air-dried at room temperature (20)(21)(22)(23)(24)(25) ∘ C) until reaching air-dried condition in well ventilated room, protected from direct sun rays. Loss on drying before the analysis was determined by applying the method indicated in the European Pharmacopoeia.…”
Section: Plant Materialmentioning
confidence: 99%
“…Quercetin, kaempferol, and isorhamnetin are assigned as markers that can be used to evaluate the quality and authenticity of G. biloba extracts and dosage forms [20,21]. Therefore, as described above, aglycones, which are used as markers, were chosen for our further investigations.…”
Section: The Identification and Quantification Of Flavonoidmentioning
confidence: 99%